Professional development program to embed inclusive and explicit teaching practices in higher education first year units : Final Report. - Brown, Claire; Vodeb, Vida Voncina; Slee, Roger; Winchester, Maxwell (Office for Learning and Teaching, 2017)
This project addressed significant issues in the practice of employing sessional staff with discipline expertise but no formal teaching qualifications as tutors in large, first year higher education units. To raise the status and quality of teaching in these units, sessional staff will be trained in a suite of inclusive, explicit teaching strategies with ongoing support provided to build a professional learning community around a quality teaching focus for tutors. Quantitative and qualitative data, including teacher observations, will measure any improvements in teaching and learning outcomes. Using a long-established US professional learning and student support system entitled AVID (Advancement via Individual Determination) this project will ascertain whether equipping tutors with explicit, inclusive pedagogies improves teaching quality and the student learning experience as measured by improvements in academic progress, retention, student engagement, student satisfaction with tutoring staff and teaching quality. Findings from this project were benchmarked with findings from AVID universities in the USA where similar projects are being conducted.